Pengembangkan Modul Digital Pengelolaan Sumber Daya Belajar Berbasis Multimedia Untuk Meningkatkan Kemandirian Belajar Mahasiswa Prodi Teknologi Pendidikan - Abd Haling; Abdul Hakim; Fajrin Baids; Sofyan Sofyan (Jurnal Ilmiah Wahana Pendidikan, 2026)
This study aims to develop, test the feasibility, and analyze the effectiveness of a multimedia-based Digital Module for Learning Resource Management in improving students' independent learning at the Educational Technology Study Program, Universitas Negeri Makassar. This study applies a Research and Development (R&D) approach by adapting a simplified Borg & Gall procedural model, which includes needs analysis, prototype development, as well as product testing and revision. Data collection instruments consist of observation sheets, interview guidelines, validation and practicality questionnaires, and learning outcome tests, which were analyzed using descriptive quantitative percentage techniques. The results showed that: (1) the validity of the module based on the assessment of material and media experts was categorized as very good and feasible to use; (2) the level of practicality based on the responses of lecturers and students indicated highly practical criteria with a user-friendly interface; and (3) the field test proved that the implementation of the digital module was significantly effective in motivating and improving students' independent learning due to its interactive and self-instructional multimedia visualization. It can be concluded that the developed multimedia-based digital module is proven valid, practical, and effective as an independent teaching material innovation in higher education.